Dopamine D1 and D3 receptor modulators restore morphine analgesia and prevent opioid preference in a model of neuropathic pain. (15th May 2019) - Rodgers, H.M.; Yow, J.; Evans, E.; Clemens, S.; Brewer, Kori L.
Abstract: A secondary consequence of spinal cord injury (SCI) is debilitating chronic neuropathic pain, which is commonly morphine resistant and inadequately managed by current treatment options. Consequently, new pain management therapies are desperately needed. We previously reported that dopamine D3 receptor (D3R) dysfunction was associated with opioid resistance and increases in D1 receptor (D1R) protein expression in the spinal cord. Here, we demonstrate that in a model of SCI neuropathic pain, adjuvant therapy with a D3R agonist (pramipexole) or D1R antagonist (SCH 39166) can restore the analgesic effects of morphine and reduce reward potential. Prior to surgery thermal and mechanical thresholds were tested in three groups of female rats (naïve, sham, SCI). After surgery, testing was repeated under the following drug conditions: 1) saline, 2) morphine, 3) pramipexole, 4) SCH 39166, 5) morphine + pramipexole, and 6) morphine + SCH 39166. Reward potential of morphine and both combinations was assessed using conditioned place preference. Following SCI, morphine + pramipexole and morphine + SCH 39166 significantly increased both thermal and mechanical thresholds. Morphine alone induced conditioned place preference, but when combined with either the D3R agonist or D1R antagonist preference was not induced. The data suggest that adjunct therapy with receptor-specific dopamine modulators can restore morphine analgesia and decrease reward potential and thus, represents a new target for pain management therapy after SCI. Highlights: Morphine responsiveness is decreased following spinal cord injury (SCI). In a model of SCI neuropathic pain adding a D3R agonist restored morphine analgesia. In a model of SCI neuropathic pain adding a D1R antagonist restored morphine analgesia. Addition of either dopamine modulator (D1 antagonist or D3 agonist) decreased reward potential of morphine.